Insiders e outsiders dos direitos humanos no Brasil: o inquérito policial frente aos direitos e as garantias constitucionais - Oliveira Filho, Enio Walcacer de (Universidade Federal do Tocantins, 2015)
This dissertation is linked to the "line of research": Jurisdiction Instruments, access to justice and human rights, the Interdisciplinary Professional Master's Program in Human Rights and Jurisdictional Provision - MPIPJDH. This line of research has as an area of concentration "Penal System and Human Rights", and its "object of study" research concerning the question of jurisdiction, in the context of criminal sciences, and the necessary development of theoretical mechanisms for deepening human rights inside a perspective of fundamental rights in the improvement of the judicial instruments for resolving criminal cases focusing on human rights and fundamental constitutional guarantees. The overall objective of this research is to comprehend the current system of police investigations materialized in the Police Inquest in Brazil. The specific objectives were: understanding and description the historical evolution of Police Inquest; identify the rights and guarantees brought by the 1988 Constitution that should be applied to the Police Inquest; study the influence of General Theory of Procedures and its its civilian characteristic for the stagnation of Criminal Procedure and result in stagnation also the Police inquest in Brazil; demonstrate the importance of the Police Inquest and its influence on judicial decisions in the Brazilian penal system. As theoretical and methodological foundations of the research was made in the first part a historical-sociological approach describing the current pre-trial investigation system at different times and its historical development. In a second step begins for a systematic study of Criminal Procedure in Brazil, the constitutional principles governing it, its structure and the interaction the general structure of Criminal Procedure, in relation to the Police Inquest and its conformity with the rights and guarantees fundamental, in this second part is used the deductive method. The dissertation is the result of an extensive literature review, historical, documentary that searched the historical roots related to the preliminary investigation procedure, the evolution of Iberian-European historical systems and their influence since the colonization of Brazil until today, seeking to understand both historicity of the Police inquest as as possible a comparison between today the current system in Brazil with the 1988 Constitution. The first chapter is a historical reconstruction of origins of the Police Inquest in the second chapter is performed a legal analysis of the constitutional model compared to the model Criminal Procedural of the Inquiry, the third a critical-comparative analysis models, the fourth a procedural analysis enables check the extensive use of inquiry as the sole basis for decisions in criminal cases. The theoretical references were the most diverse, from experts of Criminal Procedure, since the nineteenth century to more recent authors and theorists of Human Rights, Constitutionalism, Law Interpretation and critical theory, building a broader, interdisciplinary insight the theme. In the final considerations, divided into two parts, first is identified total rupture of Police inquest model with the current Brazilian constitutional order, and its incompatibility at different levels and aspects. In a second part, it proposes a total restructuring of the Police inquest model in Brazil, and the constitutionalization of the procedure.